A Pathway to Technology Integration: Eliciting Consumer's Behavioural Intention to Use Paytm Services. Issue 1 (June 2021) - Mehta, Pooja; Singla, Himanshu; Saha, Raiswa; Tyagi, Shivani
The present study integrates the technology acceptance model (TAM) and the innovation diffusion theory (IDT) for analysing consumers' intention to make use of Paytm services. It is a cross-sectional study; the data was gathered from 259 Internet consumers. The statistical tools, including structural equation modelling (SEM), are applied to understand the inter-construct relationships. The intention to use Paytm is positively influenced by a perceived ease of use, perceived usefulness and social influence. Moreover, the moderating effects of perceived risk (PR) are found to be significant on the associations among social influence, perceived ease of use and Paytm usage intentions. This study will help digital wallet service providers (DWSP), who focus on identifying the important factors for accelerating the use of mobile wallets. The findings will also facilitate the government to devise ways for augmenting cashless fund movement in the economy. Besides explaining the phenomenon of Paytm usage intentions, the study reveals the moderating role of PR with respect to various antecedents, thereby filling the gap in the existing literature.